Study on the Stress Relaxation Behavior of Large Diameter B-GFRP Bars Using FBG Sensing Technology. (9th October 2013) - Guo-wei, Li; Hua-Fu, Pei; Cheng-yu, Hong
Corrosion of steel tendons in certain aggressive environments could lead to durability problems of civil engineering. More recently, fiber-reinforced polymer (FRP) rods have been introduced in the market as tendons for prestressed concrete structures because of their lower modulus behavior. However, previous studies on the FRP mechanical time dependent behavior regarding the stress relaxation of large diameter GFRP have not been well understood. This paper investigates the influence of stress levels on the relaxation behavior of a GFRP bar griped with a seamless pipe under sustained deformations ranging from 30% to 60% of its ultimate strain. In order to study the behavior of stress relaxation, two basalt-glass fiber hybrid composite (B-GFRP) bars were developed and instrumented with fiber Bragg grating (FBG) strain sensors. It can be found that the test results reveal that the seamless pipe grip method can undertake 70% of ultimate tensile load of the B-GFRP bar, which can satisfy the requirement of stress relaxation of B-GFRP bar subjected to prestress. The model proposed for evaluating stress relaxation ratio can reflect the influences of the nature of B-GFRP bar and the property of grip method.